2014
DOI: 10.1017/s1461145714000169
|View full text |Cite
|
Sign up to set email alerts
|

Role of 6-monoacetylmorphine in the acute release of striatal dopamine induced by intravenous heroin

Abstract: After injection, heroin is rapidly metabolized to 6-monoacetylmorphine (6-MAM) and further to morphine. As morphine has been shown to increase striatal dopamine, whereas 6-MAM has not been studied in this respect, we gave i.v. injections of 3 μmol 6-MAM, morphine or heroin to rats. Opioids were measured in blood, and dopamine and opioids in microdialysate from brain striatal extracellular fluid (ECF), by UPLC-MS/MS. After 6-MAM injection, 6-MAM ECF concentrations increased rapidly, and reached Cmax of 4.4 μM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 33 publications
1
56
0
Order By: Relevance
“…Nevertheless, both in the presence and absence of mAb we report a more profound psychomotor effect and higher 6-MAM levels in brain after injection of heroin compared with 6-MAM, as previously indicated after both subcutaneous and intravenous administration Gottås et al, 2014). Heroin itself is highly lipophilic and may rapidly cross the BBB for subsequent deacetylation into 6-MAM (Oldendorf et al, 1972;Umans and Inturrisi, 1981).…”
Section: Pharmacological Potential Of a Mab Against 6-mamsupporting
confidence: 79%
See 1 more Smart Citation
“…Nevertheless, both in the presence and absence of mAb we report a more profound psychomotor effect and higher 6-MAM levels in brain after injection of heroin compared with 6-MAM, as previously indicated after both subcutaneous and intravenous administration Gottås et al, 2014). Heroin itself is highly lipophilic and may rapidly cross the BBB for subsequent deacetylation into 6-MAM (Oldendorf et al, 1972;Umans and Inturrisi, 1981).…”
Section: Pharmacological Potential Of a Mab Against 6-mamsupporting
confidence: 79%
“…Previous work in our laboratory has shown that 6-MAM is the predominating metabolite in brain and blood after subcutaneous and intravenous heroin administration in mice and rats, respectively, indicating that 6-MAM is the main contributor to acute heroin effects Gottås et al, 2013). In addition, the psychomotor-stimulating effect and dopamine peak levels coincided with the rising concentration of 6-MAM in brain tissue, at a time when heroin was no longer detectable Gottås et al, 2013Gottås et al, , 2014. Furthermore, pharmacokinetic studies have indicated that heroin is mainly metabolized outside the brain .…”
Section: Introductionmentioning
confidence: 86%
“…A 2-min interval was applied when studying heroin and its metabolites 6-acetylmorphine and morphine in rats, giving a very high time resolution of the pharmacokinetics of brain uptake of the compounds in relation to pharmacological effect (88,89).…”
Section: Trade-offs When Designing a Microdialysis Studymentioning
confidence: 99%
“…One animal study found that in the postnatal development of mice, the BBB penetration of morphine decreased while that of diacetylmorphine did not, indicating a possible greater passive diffusion capacity of diactylemorphine (192). Although morphine is often assumed to be the active metabolite responsible for heroin's pharmacodynamic effects, a number of animal studies have proposed that 6-MAM may in fact be more important (193,194).…”
Section: Diacetylmorphinementioning
confidence: 99%